Role of Inflammation in Vascular Disease-Related Perivascular Adipose Tissue Dysfunction - Chen, Yaozhi; Qin, Zeyu; Wang, Yaqiong; Li, Xin; Zheng, Yang; Liu, Yunxia (Frontiers in Endocrinology, 2021)
Perivascular adipose tissue (PVAT) is the connective tissue around most blood vessels throughout the body. It provides mechanical support and maintains vascular homeostasis in a paracrine/endocrine manner. Under physiological conditions, PVAT has anti-inflammatory effects, improves free fatty acid metabolism, and regulates vasodilation. In pathological conditions, PVAT is dysfunctional, secretes many anti-vasodilator factors, and participates in vascular inflammation through various cells and mediators; thus, it causes dysfunction involving vascular smooth muscle cells and endothelial cells. Inflammation is an important pathophysiological event in many vascular diseases, such as vascular aging, atherosclerosis, and hypertension. Therefore, the pro-inflammatory crosstalk between PVAT and blood vessels may comprise a novel therapeutic target for the prevention and treatment of vascular diseases. In this review, we summarize findings concerning PVAT function and inflammation in different pathophysiological backgrounds, focusing on the secretory functions of PVAT and the crosstalk between PVAT and vascular inflammation in terms of vascular aging, atherosclerosis, hypertension, diabetes mellitus, and other diseases. We also discuss anti-inflammatory treatment for potential vascular diseases involving PVAT.